Analyzing students’ statistical literacy skills based on gender, grade, and educational field - Riwayani Riwayani; Edi Istiyono; Supahar Supahar; Riki Perdana; Soeharto Soeharto (International Journal of Evaluation and Research in Education (IJERE), 2024)
Statistical literacy is fundamental competence to think critically and to conclude information based on data. This study aims to describe students’ statistical literacy according to gender, grade, and educational field. This research was a quantitative method with a cross-sectional design by explaining and analyzing the results using Rasch modeling, and students’ statistical literacy was categorized and described according to statistical literacy topics, gender, student grade level, and educational field. The respondent of this study was 271 students obtained through the stratified random sampling in Yogyakarta’s senior high school. The result of this study confirmed that the statistical literacy skills of students are still at a low level. The lowest aspect is the scope of conclusions, while the highest aspect is data production (medium level). There are no significant differences in statistical literacy skills based on gender and class. However, there are significant differences in statistical literacy based on field education. It indicates that policymakers or teachers should improve students’ statistical literacy skills by training or applying a learning model that focuses explicitly on statistical literacy skills.